Evaluation of Antioxidant Property of Curcumin-loaded Nanoemulsion - Adnan, Nurul Aini; Mohd Kassim, Angzzas Sari; A. Raza, Aliff Hisyam (Progress in Engineering Application and Technology, 2022)
Antioxidants are substances that scavenge free radicals. Sources of antioxidants can be produced either from natural or synthetic. However, for the past few decades, the health concern towards the carcinogenicity of synthetic antioxidants has grown among skincare consumers, resulting in the increasing demand for natural antioxidants. Therefore, the study proposed to produce a curcumin-loaded nanoemulsion and evaluate its antioxidant property. The formulation of nanoemulsion involves the oil in water (o/w) emulsion type through the phase inversion temperature (PIT) method, that is used to produce nano-structured curcumin with high solubility, high bioavailability, high total phenolic contents and antioxidant activity. Nanoemulsion composed of black pepper oil and non-ionic surfactant Tween 20, with a mean droplet size ranging from 310 to 720 nm, was formulated for various concentrations of the oil and surfactant. Nano-Cur has obtained a particle size of 320 nm when the following optimal conditions were adopted as the oil-surfactant ratio (0.5:9.5). Inverter Microscope with Flouresence has been used to determine the particle size distribution. Antioxidant activity tests were applied to the pure extracts, Nano-CUR, and the mixture of Tween 20 + BP oil. Results demonstrated that Nano-CUR has maximum antioxidant activity (94.6 ± 0.37% RSA) with the highest reading of total phenolic content (2.58 ± 0.01 mg GAE/g). The correlation between total phenolic content and antioxidant activity also showed a positive correlation where both analyses are directly proportional to each other. Overall, the study provides helpful information on curcumin-loaded nanoemulsion, which may benefit more natural-based products in the future.